PERLINDUNGAN HUKUM MENURUT LAWRENCE M FRIEDMAN TERHADAP PELAKSANAAN PROGRAM KESERTAAN PRIA BERDASARKAN UNDANG-UNDANG NOMOR 52 TAHUN 2009 TENTANG PERKEMBANGAN KEPENDUDUKAN DAN PEMBANGUNAN KELUARGA - Merlin Swantamalo Magna; Ainun Nadhifah (LPSDI Bina Patria, 2024)
This review discusses legal protection according to Lawrence M. Friedman to the Implementation of the Men's Participation Program based on Law Number 52 of 2009 concerning Population Development and Family Development has contained legal protection or has not been analyzed based on the legal structure, legal substance and legal culture. The results of the study show that the legal structure of family planning organizing institutions at the central and provincial levels, namely BKKBN, while at the district/city level it is integrated into the Regional Apparatus Organization based on the policies of each region so that the achievements of male family planning users in each region are different. In terms of legal substance, there is a lack of special regulations in the form of implementing regulations regarding the form of male family planning and a legal umbrella for new types of male contraception. Meanwhile, in terms of legal culture, Indonesian people still consider taboos related to male contraception and the existence of MUI decisions related to vasectomy which cannot be applied in general but are conditionally enforced. Therefore, there is no legal protection related to the implementation of male family planning.